Extraction and characterization of fatty acids from the leaves and stems of Clinacanthus nutans using supercritical carbon dioxide and Soxhlet method - Sahena, Ferdosh; Kamaruzzaman, Yunus; A. Rashid, Mohammad; Sarker, Md. Zaidul Islam (Bentham Science, 2020)
Background: The composition and bioactivity of natural plant extracts strongly depend on the extraction technique employed. Clinacanthus nutans Lindau (C. nutans) is a well-known medicinal plant in South-East Asia that has been traditionally used for the treatment of various diseases. Several conventional methods have been using for extraction of bioactive compounds from C. nutans. However, extraction of fatty acids using supercritical carbon dioxide was not reported yet from this medicinal herbs. Objective: The main objective of the study is to examine the potential of supercritical carbon dioxide (scCO2) extraction of fatty acids from leaves and stems of C. nutans. Method: Fatty acid compositions were determined from leaves and stems of C. nutans oil extracted by scCO2 (temperature 45-65 °C, pressure 25-35 MPa), and compared to the results of Soxhlet extraction. Results: Supercritical CO2 extraction shows the highest oil recovery in both leaves (3.7%) and stems (1.6%) at pressure 35 MPa, temperature 65 °C and 2 ml/min flow rate, which was closer to the yield of Soxhlet. The scCO2 yields presented a higher percentage of polyunsaturated fatty acids (PUFA), especially linoleic acid (C18:2n-6). Palmitic acid ranging from 42%- 47% in leaves and stems of C. nutans was found dominant saturated fatty acids (SFA) in both scCO2 and Soxhlet method. Conclusion: The current results indicate that leaves and stems of C. nutans could be a potential source of fatty acids especially biologically active compounds.